1997
DOI: 10.1159/000189529
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Attack Complex and Membrane Cofactor Protein Are Related to Tubulointerstitial Inflammation in Various Human Glomerulopathies

Abstract: Immunohistochemical analysis of the membrane attack complex (MAC) and the membrane cofactor protein (MCP) was performed on the tubuli and cortical vessels of 46 kidney biopsies with various types of human glomerulopathies. Irrespective of the type of glomerulopathy, significant correlations between tubular MAC and interstitial lymphomonocyte infiltration (p < 0.001) and interstitial volume (p < 0.02) were found. Tubular MCP was significantly overexpressed at the site of MAC deposition (p < 0.002). There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 23 publications
5
35
0
1
Order By: Relevance
“…In fact, membrane MCP in the kidney is also up-regulated in some disease states such as IgA nephropathy (28). Another report (29) has suggested that tubular MCP is overexpressed at the deposition site of the membrane attack complex. The levels of sMCP were increased in patients with malignancy (19) and autoimmune diseases such as systemic lupus erythematosus (30).…”
Section: Urinary Cd46 In Glomerulonephritismentioning
confidence: 99%
“…In fact, membrane MCP in the kidney is also up-regulated in some disease states such as IgA nephropathy (28). Another report (29) has suggested that tubular MCP is overexpressed at the deposition site of the membrane attack complex. The levels of sMCP were increased in patients with malignancy (19) and autoimmune diseases such as systemic lupus erythematosus (30).…”
Section: Urinary Cd46 In Glomerulonephritismentioning
confidence: 99%
“…15 There is a spatial association between complement deposition and tissue injury in the kidneys of patients with proteinuric nephropathies. 16 In experimental proteinuria, genetic deficiency, [17][18][19] or depletion or inhibition 20,21 of complement reduces the level of tubulointerstitial injury and preserves renal function. 22 These data support a role for both C5b-9 19 and the anaphylotoxin C5a.…”
mentioning
confidence: 99%
“…For example, elevated urinary C5b-9 concentrations are found in proteinuric patients (2), urinary C5b-9 was shown to reflect disease activity in an experimental model of membranous glomerulonephritis better then proteinuria (3), C5b-9 depletion in experimental nephropathy reduces proteinuria (4), and C5b-9 is formed at sites of tubulointerstitial injury (5,6).…”
mentioning
confidence: 99%